A Systematic Review of the Role of Robotics in Plastic and Reconstructive Surgery—From Inception to the Future - Dobbs, Thomas D.; Cundy, Olivia; Samarendra, Harsh; Khan, Khurram; Whitaker, Iain Stuart (Frontiers in Surgery, 2017)
Background The use of robots in surgery has become commonplace in many specialties. In this systematic review we report on the current uses of robotics in plastic and reconstructive surgery and looks to future roles for robotics in this arena. Methods A systematic literature search of Medline, EMBASE and Scopus was performed using appropriate search terms in order to identify all applications of robot-assistance in plastic and reconstructive surgery. All articles were reviewed by two authors and a qualitative synthesis performed of those articles that met the inclusion criteria. The systematic review and results were conducted and reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta Analysis (PRISMA) guidelines. Results A total of 7904 articles were identified for title and abstract review. Sixty-eight studies met the inclusion criteria. Robotic assistance in plastic and reconstructive surgery is still in its infancy, with areas such as trans-oral robotic surgery (TORS) and microvascular procedures the dominant areas of interest currently. A number of benefits have been shown over conventional open surgery, such as improved access and greater dexterity, however these must be balanced against disadvantages such as the lack of haptic feedback and cost implications. Conclusion The feasibility of robotic plastic surgery has been demonstrated in several specific indications. As technology, knowledge, and skills in this area improve, these techniques have the potential to contribute positively to patient and provider experience and outcomes.